2015
DOI: 10.1039/c5ra17668a
|View full text |Cite
|
Sign up to set email alerts
|

Direct metal-free synthesis of diarylamines from 2-nitropropane via the twofold C–H functionalization of arenes

Abstract: Synthesis of symmetric diarylamines via a twofold intermolecular electrophilic C-H functionalization of electron-rich arenes by umpolung-activated nitroalkane in polyphosphoric acid is demonstrated. Synthesis of symmetric diarylamines via a twofold intermolecular electrophilic C--H functionalization of electron--rich arenes by umpolung--activated nitroalkane in polyphosphoric acid is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…1 , eqn (2)), 4 , 5 (iii) arylation of anilines involving directing-group assisted aromatic C–H bond activation ( Fig. 1 , eqn (3)), 6 and (iv) dehydrogenative aromatization ( Fig. 1 , eqn (4)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 , eqn (2)), 4 , 5 (iii) arylation of anilines involving directing-group assisted aromatic C–H bond activation ( Fig. 1 , eqn (3)), 6 and (iv) dehydrogenative aromatization ( Fig. 1 , eqn (4)).…”
Section: Introductionmentioning
confidence: 99%
“…Although arylation of anilines with arenes through directing group-assisted aromatic C–H bond activation has recently been developed ( Fig. 1 , eqn (3)), 6 most of the reported systems require (super)stoichiometric amounts of organic reagents or metal-based oxidants, and exhibit a limited scope of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that upon heating in polyphosphoric acid, the nitroalkanes 1 convert into the phosphorylated nitronates 2, which exhibit strong electrophilic properties. This allowed for the employment of these species in reactions wherein electron-rich arenes serve as carbon-based nucleophilies [38][39][40]. It was also discovered that the nucleophilic amines 3 can be successfully employed in this type of transformations as well, providing the amidinium intermediates 4, which are susceptible to a variety of subsequent cyclizations.…”
Section: Resultsmentioning
confidence: 99%
“…This unusual species can be used to design a number of one-pot multi-step transformations involving various carbon-based nucleophiles. [17][18][19] The utilization of nucleophilic amines was also demonstrated. [20][21][22][23][24] Mechanistically, the latter process is related to the classical Nef reaction, [25][26][27] employing aniline [20][21][22][23] or hydrazine 24 species 8 instead of water.…”
Section: Resultsmentioning
confidence: 99%